AIP Conference Proceedings 2009
DOI: 10.1063/1.3099227
|View full text |Cite
|
Sign up to set email alerts
|

Supergranulation Scale Convection Simulations

Abstract: Abstract.Results of realistic simulations of solar surface convection on the scale of supergranules (96 Mm wide by 20 Mm deep) are presented. The simulations cover only 10% of the geometric depth of the solar convection zone, but half its pressure scale heights. They include the hydrogen, first and most of the second helium ionization zones. The horizontal velocity spectrum is a power law and the horizontal size of the dominant convective cells increases with increasing depth. Convection is driven by buoyancy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
33
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 2 publications
3
33
0
Order By: Relevance
“…This would imply that the network field is not strictly a passive tracer of the supergranular flow, but rather may play an active dynamic role in supergranular scale selection by inducing radiative perturbations at depth where the density and pressure scale heights are greater. This may provide an explanation for why strictly hydrodynamic simulations have difficulty unambiguously obtaining supergranular scales (Ustyugov 2008;Stein et al 2009), though domain sizes are also currently still quite restrictive.…”
Section: Resultsmentioning
confidence: 99%
“…This would imply that the network field is not strictly a passive tracer of the supergranular flow, but rather may play an active dynamic role in supergranular scale selection by inducing radiative perturbations at depth where the density and pressure scale heights are greater. This may provide an explanation for why strictly hydrodynamic simulations have difficulty unambiguously obtaining supergranular scales (Ustyugov 2008;Stein et al 2009), though domain sizes are also currently still quite restrictive.…”
Section: Resultsmentioning
confidence: 99%
“…For the Sun, we have deep (20 Mm) convection calculations (Stein et al 2009) and the determination of the mass mixing length is straightforward, as shown in Figure 3. From this we see that the ratio of the mass mixing length to the pressure scale height, α P , is nearly constant with depth in the interior of the convection zone until the bottom boundary is approached.…”
Section: Resultsmentioning
confidence: 99%
“…The mass mixing length, the distance over which, because of mass conservation, most of the ascending fluid turns over and starts to descend, is the inverse of the logarithmic derivative of the unidirectional mass flux (Stein et al 2009):…”
Section: Mass Mixing Lengthmentioning
confidence: 99%
“…Simple models like the mixing-length theory or plume dynamics (Rieutord & Zahn 1997) do not predict any special spectral feature when the scale (horizontal or vertical) grows. Hydrodynamic numerical simulations like the recent ones of Stein et al (2009) seem to go in the same direction and do not exhibit any spectral feature reminiscent of supergranulation (see also Nordlund et al 2009). However, kinetic energy spectra derived from the radial velocity measured by SOHO/MDI (i.e.…”
Section: Introductionmentioning
confidence: 95%
“…Despite several attempts, supergranulation has not been identified in large-eddy or direct numerical simulations (e.g. Rieutord et al 2002;Rincon et al 2005;Stein et al 2009). Its origin remains unknown, although some scenarios have been proposed.…”
Section: Introductionmentioning
confidence: 99%